PROFIT MANAGEMENT ANALYSIS OF THE CONSUMER GOODS INDUSTRY IN INDONESIA: SHARIA VERSUS NON-SHARIA SHARE - Titin Agustin Nengsih; Mellya Embun Baining; Muhammad Riyadi Dwi Atmojo (International Journal of Islamic and Social Sciences (ISOS), 2021)
Profit management is carried out by the company to achieve the manager's motivation to achieve profit targets which are applied in managing financial statements. Many factors can affect profit management. This study aims to determine the factors that influence profit management in the consumer goods industry sector, at sharia and non-sharia. This data uses the financial reports and the annual reports of manufacturing companies at IDX (Indonesian Stock Exchange) in the 2016-2019 with 19 sharia companies and 10 non-sharia companies. This study uses the Multiple Linear Regression analysis with dependent variables: tax planning, current tax expense, profitability, audit committee, company size, managerial ownership, and leverage. The results of this study show all the variables both in sharia and nonsharia manufacturing companies in the consumer goods industry in the 2016-2019 influence together the profit management. The coefficient of determination for these models is 72% at sharia shares and 51% at non-sharia shares. According to t-test, it shows that tax planning, current tax expense, and managerial ownership influence profit management in sharia shares and only the company size influences profit management in non-sharia shares at manufacturing companies in the consumer goods industry in Indonesia at the 2016-2019.